Outcomes of a Comprehensive Retention Strategy for Youth With HIV After Transfer to Adult Care in the United States. Issue 7 (July 2019) - Griffith, David; Jin, Lillian; Childs, Jocelyn; Posada, Roberto; Jao, Jennifer; Agwu, Allison
Abstract : Background: The retention of youth living with HIV (YLHIV) in adult care after transfer from pediatric care in the United States is a challenge. A targeted comprehensive retention strategy (CRS) may improve retention among YLHIV. Methods: A retrospective cohort study of YLHIV after transfer from pediatric to adult care for patients with at least 1 adult visit at 2 urban HIV care programs in the United States employing CRSs with internal medicine/pediatrics-trained providers, peer navigators, social workers and mental health resources. Primary outcomes were successful retention in care after transfer (≥2 provider visits in the adult clinic ≥90 days apart within 1 year of transfer) and successful transition (successful retention plus a stable HIV viral load (VL) defined as VL 1 year after transfer that was less than or equal to the VL obtained at or immediately before transfer). Logistic regression assessed factors associated with successful transition. A subgroup analysis was performed to examine rates of successful transfer and linkage from pediatric to adult clinics (attending at least 1 adult visit after transition). Results: Of the 89 patients included in the study, 79 (89%) patients had successful retention and 53 (60%) had successful transition to the adult program. Factors associated with successful transition included non-African American race [adjusted odds ratio (aOR) = 11.26, 95% confidence interval (CI): 1.32–95.51], perinatal HIV (aOR = 8.00, 95% CI: 1.39–46.02) and CD4 count > 500 cells/mm 3 (aOR = 5.22, 95% CI: 1.54–17.70). Of those who were retained, 53/79 (67%) had stable or improved virologic control at 1 year after transition. In a subgroup analysis, 54/56 (96%) patients who were targeted to transition successfully linked to adult care. Conclusions: Overall, YLHIV in the United States engaged in a CRS program appear to have high retention rates but suboptimal virologic control after transfer from pediatric HIV care. Abstract : Supplemental Digital Content is available in the text.